In door physical education measured by heart rate monitor: a case study in Portugal - Wang, G. Y. (2005)
Reports indicated that children are spending too much time being physically inactive during physical education classes and many school physical education programs are not meeting the recommendation. The purpose of this study was to investigate the physical activity levels in Portuguese indoor physical education classes. Methods. The physical activity levels of 28 Portuguese 7[th] grade children were assessed by heart rate monitor during their indoor physical education classes. Results. The study showed that much physical education class time had been wasted, and less than 70% of physical education class time had actually been used in classes. On average, 14.4 min of 45-min physical education classes and 27.9 min of 90-min physical education classes had been spent in MVPA with children's heart rates above 139 bpm; 6.7 min of 45-min physical education classes and 15.7 min of 90-min physical education classes had been spent in VPA with children's heart rates above 159 bpm. Children engaged in more MVPA, VPA, and continuous bouts of physical activity in 90-min physical education classes than those of 45-min physical education classes. There were no significant differences in activity levels between genders in co-educational indoor physical education classes. Conclusion. This indoor PE class study supports the results that children are less active during school physical education classes. Both the quantity and the quality of school physical education needs to improve to encourage children to engage in a substantial amount of physical activity both inside and outside school.